Lo comunitario en las radios comunitarias: sentidos en juego (2013)
What’s the community sense in the Latin American community radio? Beyond thelegal or academic definitions done outside, the community sense is constructed andlived into the broadcasting production daily work at these media. From an anthropological approach to the community radio in Mexico and Colombia, the author apprehends and documents the community sense under its everyday programming.